Dissociative Identity Disorder and the Law: Guilty or Not Guilty? - Kabene, Stefane M.; Balkir Neftci, Nazli; Papatzikis, Efthymios (Frontiers in Psychology, 2022)
Dissociative identity disorder (DID) is a dissociative disorder that gained a significant rise in the past few decades. There has been less than 50 DID cases recorded between 1922 and 1972, while twenty thousand cases are recorded by 1990 (Showalter, 1997). Therefore, it becomes of great significant to assess the various concepts related to DID to further understand the disorder. The current review has a goal of understanding whether an individual suffering from DID is legally responsible for the committed crime, and whether or not he or she can be considered competent to stand trial. These two questions are to be raised in understanding DID, by first shedding a light on the nature of the disorder and second by examining the past legal case examples. Despite the very nature of the disorder is characterized by dissociative amnesia and the fact that the host personality may have limited or no contact with the alters, there is no consensus within the legal system whether the DID patients should be responsible for their actions. Further to that, courts generally deny the insanity claims for DID suffering patients. In conclusion, more studies in the field are suggested to incorporate primary data into research, as the extensive reliance on secondary data forces us to believe the conclusions that were previously made, and no opportunity to verify those conclusions is present.